Pump-turbine Rotor-Stator Interaction Induced Vibration: Problem Resolution and Experience. Issue 1 (June 2021) - Zhang, F; Lowys, PY; Houdeline, JB; Guo, XD; Hong, P; Laurant, Y
Abstract: Pressure pulsations induced by rotor-stator interaction (RSI) phenomenon are one of the major sources of excitation resulting in severe vibrations of pump-turbines and powerhouses. By now, many articles focus mainly on the RSI mechanism by methods of theoretical analysis, fluid-structure calculation and model test verification. There are few reports published on equipment and powerhouse vibrations induced by RSI. Therefore, in this paper we took a real RSI induced problem at Zhanghewan (ZHW) pumped storage power plant (PSPP). We employed frequency spectrum technology on signals of powerhouse vibrations and pressure pulsations in stable and transient processes, combined eigen-frequency measurement and numerical calculation of powerhouse localities, and then confirmed that partial powerhouse resonated with RSI induced pressure pulsation in the vaneless area (gap between guide vanes and runner blades). We statistically evaluated the relationship between the ratio of guide vane pitch diameter D0 to the high-pressure runner diameter D1 and vaneless area pressure pulsation from many PSPPs in China, and proposed solutions that new runner should use. The runner alteration work was successful. Model tests and field measurements show that vaneless pressure pulsation decreases and the powerhouse shows acceptable vibration levels. Many experiences were accumulated during this work, including that from an engineering perspective by enlarging the vaneless area it is possible to lower RSI induced pressure vibrations. Also, much attention should be paid on local anti-vibration calculations in the powerhouse designing period. Our research and review provide a new perspective for designing, refurbishing, rehabilitating of pump-turbines.